New 2D Structural Materials: Carbon–Gallium Nitride (CC–GaN) and Boron–Gallium Nitride (BN–GaN) Heterostructures—Materials Design Through Density Functional Theory - Elloh, V.W.; Yaya, A.; Gebreyesus, G.; Dua, P.; Mishra, A.K. (ACS Omega, 2019)
New class of ternary nanohetrostructures have been proposed by mixing 2D gallium nitride (GaN) with graphene and 2D hexagonal boron nitride (BN) with an aim towards desgining innovative 2D materials for applications in electronics and other industries. The structural stability and electronic properties of these nanoheterostructures have been analyzed using first-principles based calculations done in the framework of density functional theory. Different structure patterns have been analyzed to identify the most stable structures. It is found to be more energetically favorable that the carbon atoms occupy the positions of the nitrogen atoms in a clustered pattern in CC-GaN heterostructures, whereas boron doping is preferred in the reverse order, where isolated BN and GaN layered configurations are preferred in BN-GaN heterostructures. These 2D nanoheterostructures are energetically favored materials with direct band gap and have potential application in nanoscale semiconducting and nanoscale optoelectronic devices.